(untitled) (Journal of Parents and Teachers, 1996)
The article highlights the importance of educators in the transmission of culture and the personalization of teaching. The use of technology to address social problems and foster critical thinking is emphasized. In addition, the need for an education that promotes justice and solidarity is emphasized.